Estimation of In-Situ Stress – Experiemtnal Trials on Kaiser Effect and Hydrofracturing Tests - Jayanthu, Singam (Journal of Mines, Metals and Fuels, 2022)
In the present paper, an acoustic emission trend in the Kaiser effect of rocks was studied and possibility of its application in the estimation of in-situ rock mass stress was explored. Several methods have been proposed for estimating in-situ stress in the laboratory from rock core samples collected from the boreholes. Among them, acoustic emission (AE) method based on Kaiser effect is the simplest. Conventionally, in-situ stress is estimated by plotting cumulative events versus stress. The change in the slope of the curve is an indicator of the Kaiser stress. In the present study, borehole drilled samples from five sites were investigated in the laboratory by AE method for which the in-situ stress was already measured by hydrofracturing method. A plot of cumulative events versus stress indicated three types of trend and is named as type 1, 2 and 3. It is easy to identify the Kaiser stress if the trend is of type 1. Types 2 and 3 trends do not show any perceptible change in the slope of the curve and it is impossible to identify the Kaiser stress. Since most of the samples showed type 2 and type 3 trend, to estimate the Kaiser stress, other AE parameters namely ring down count, energy and absolute energy of the events were used. Among these parameters, absolute energy plot showed more significant change in the slope, and hence preferred for identification of the Kaiser stress.